TRADITIONS AND TRANSFORMATIONS: THE ROLE OF MADRASAHS AND SUFI ORDERS IN THE CULTURAL AND SOCIAL LIFE OF MEDIEVAL UZBEKISTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article explores the role of madrasahs and Sufi orders in the cultural and social life of medieval Uzbekistan. These institutions served as centers of knowledge, moral guidance, and social cohesion, leaving a lasting impact on the region’s cultural heritage.
Keywords: madrasa, sufi orders, medieval Uzbekistan, culture, social life, traditions, transformations, religion, education.